Off-Record Politeness Strategies Used by the EFL Teachers for Blended Classroom - Aeni, Nur; Muthmainnah, Muthmainnah; Strid, John Evar; Apriani, Eka (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study was to determine the politeness strategies used by teachers when teaching English in coeducational classrooms and the impact of these strategies on students. We focused on analyzing teachers' verbal perceptions of off-record politeness and explained the implications of politeness as found in two English lesson recordings. Researchers employed targeted selection and informative qualitative studies to obtain data. Data were collected through interviews and observations. Researchers transcribed the conversation and applied the theory of Brown and Levinson to analyze it. The subjects of this study were high school English teachers in South Sulawesi. Researchers observed classrooms by recording teacher activity and analyzing it using The theory of etiquette techniques by Brown and Levinson. Consequently, the effects on students in learning are motivation, student attitudes (emotional), respect for teachers, self-confidence, activity, participation in the teaching and learning process, and integrity.